Teacher competencies necessary for teaching chemistry in the context of Twenty-first century skills - Alamry, Ahmad Mohammed; Bin Ibrahim, Manal Hassan (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the degree of possession of chemistry teachers in the Wadi Al-Dawasir Education Department for teaching competencies in the light of the twenty-first century skills, and to identify the differences in teaching competencies that are due to the variables of experience and academic qualification. (33) teachers, and the researcher relied on the descriptive approach (survey study) as it is appropriate for this research and answers his questions. The questionnaire was used as a tool for the study, and the study concluded that the teaching competencies in the light of the skills of the twenty-first century included three competencies: (competencies of planning, implementation). It also found that the degree of chemistry teachers’ possession of teaching competencies in the light of the twenty-first century skills was very high in the total score. It was significant in the areas of planning, implementation, evaluation. The study recommended several recommendations, the most important of which is directing leaders and those responsible for education to pay attention to technological competencies, imparting them to teachers, and monitoring their use of them during teaching.